ANALISIS KOMPETENSI PROFESIONAL GURU DI SMK NEGERI KABUPATEN TANA TORAJA - Edwar Luden; Hamsu Abdul Gani; Purnamawati (UNM Journal of Technology and Vocational, 2023)
This study aims to examine: (1) the level of professional competence of teachers at SMKN (public vocational high Schools) in Tana Toraja Regency, (2) the level of learning management of teachers at SMKN in Tana Toraja Regency, (3) the level of professional development of teachers at SMKN in Tana Toraja Regency, (4) the influence of learning management on professional competence of teachers at SMKN in Tana Toraja Regency, (5) the influence of professional development on professional competence of teachers at SMKN in Tana Toraja Regency and (6) The influence of learning management, professional development collectively on professional competence of teachers at SMKN in Tana Toraja Regency. The data collection tecnhique employed a questionnaire sheet. The data analysis technique used was quantitative descriptive analysis. The results of the study reveal that the level of professional competence of teachers at SMKN in Tana Toraja Regency reaches 95.05%. The level of learning management of teachers at SMKN in Tana Toraja Regency reaches 94.95%. There is an influence of learning management on professional competence of teachers at SMKN in Tana Toraja Regency by 68.5%. There is an influence of professional development on professional competence of teachers at SMKN in Tana Toraja Regency by 64.1%. There is a significant influence of learning management and professional development collectively on professional competence of teachers at SMKN in Tana Toraja Regency by 77.2%. The recommendations to teachers at SMKN in Tana Toraja is they should improve their professional competence, especially in the use of learning media and to update knowledge and skills according to technological developments.